Teaching Learning Process Of English At Mts N Simo: A Micro Ethnographic Study - Istik Maludin, Nur; , Dr. Anam Sutopo, M.Hum; , Dr. Phil. Dewi Candraningrum, M.Ed (2015)
ABSTRACT: English plays the important role as a means of international communication. The teaching learning process of English bridges the students to master English. The main problem of this study is how English teaching learning process is applied in MTs N Simo. The problems of this study are what is syllabus used in MTs N Simo,what are the learning objectives, what are the instructional materials, what are the teaching designs including the teaching procedure, the classroom activities, the teacher's roles, the student's roles, what are the teaching medias,what are the evaluation models, and what are the strengths and weaknesses. The objectives of this study briefly disclose the English teaching learning process in MTs N Simo including to describe syllabus used in MTs N Simo, to reveal the learning objectives, to explain the instructional materials,to describe the teaching designs consisting of teaching procedure, classroom activities, teacher's roles, student's roles, teaching medias,to describe the evaluation models, and to unearth the strengths and weaknesses.This thesis uses qualitative research that is an ethnographic study including description of setting, data and source of data, method of collecting data,data credibility, and technique of data analysis. The results of this study are the syllabus is School Based Curriculum (KTSP);the learning objectives are general and specific ones;the instructional materials are visual aids, audio aid, and computer assisted learning;the teaching procedures are BKF-MT-JCT-ICT;the classroom activities are reading aloud, question and answer exercise, getting student to self-assess,conversational practise,fill in the blank, dictation,and paragraph writing;the teacher's roles are as facilitator,organizer,assessor, prompter,participant,resource, tutor ,and observer; the student's roles are plan their learning program, responsible what they do in the classroom,evaluate their learning progress,peer other learners, a member of learning interaction,and learn from teacher, student, and other learning sources;the teaching medias are printed medias involving dictionary, pieces of paper and colourful envelopes, while unprinted medias are laptop, LCD Projector,speakers active; the evaluation portrays the types of evaluation including formative and summative evaluations; and there are some strengths and weaknesses in the teaching learning process of English at MTs N Simo. Starting out from the finding, discussion,conclusion,and implication,the researcher suggests for the English teachers to consider the students as the learning subjects by involving the students in the active learners. The various methods and techniques of teaching should be well prepared by the English teachers to avoid the uninteresting teaching learning process. The writer, then, suggests the future researchers to develop such kind of the study in the other disciplines.